Stored root carbohydrates can maintain root respiration for extended periods. Issue 1 (27th December 2017) - Aubrey, Doug P.; Teskey, Robert O.
Summary: Tight coupling between below‐ground autotrophic respiration and the availability of recently assimilated carbon (C) has become a paradigm in the ecophysiological literature. Here, we show that stored carbohydrates can decouple respiration from assimilation for prolonged periods by mobilizing reserves from transport roots to absorptive roots. We permanently disrupted the below‐ground transfer of recently assimilated C using stem girdling and root trenching and measured soil CO2 efflux for over 1 yr in longleaf pine ( Pinus palustris ), a species that has large reserves of stored carbohydrates in roots. Soil CO2 efflux was not influenced by girdling or trenching through the 14‐month observation period. Stored carbohydrate concentrations in absorptive roots were not affected by the disrupted supply of current photosynthate for over 1 yr; however, carbohydrate concentrations in transport roots decreased. Our results indicate that root respiration can be decoupled from recent canopy assimilation and that stored carbohydrates can be mobilized from transport roots to absorptive roots to maintain respiration for over 1 yr. This refines the current paradigm that canopy assimilation and below‐ground respiration are tightly coupled and provides evidence of the mechanism and dynamics responsible for decoupling the above‐ and below‐ground processes.